Analysis of Falling Block Characteristics in Salt Caverns Energy Storage Space - Shengwei Dong; Taian Fang; Jifang Wan; Shan Wang; Yanqi Zhao; Xiaowen Chen; Xiaofeng Yang; Yangqing Sun (Energies)
In the current global energy sector where energy storage technology is highly regarded, the development of storage technology is crucial. Utilizing specific underground space for the storage of oil and gas and other energy sources is the direction of future development, and the space formed by deep-salt-mine water dissolution extraction has gradually become the preferred choice. However, in actual operation, multi-layer salt cavities are prone to collapse of interlayer and bending of pipes, seriously affecting the progress, quality, and safety of the entire energy storage space construction. Therefore, based on relevant principles, a targeted experimental platform was established, by taking photos and measurements of the falling process of specific falling objects, simulating the situation of falling objects in actual energy storage spaces and their impact on related components. In-depth research was conducted on the probability of falling objects hitting the inner pipe and the horizontal impact force under different conditions, and the experimental results were verified by rigorous numerical simulation analysis. The research results show that falling objects impacts can cause related components to bend, with the maximum impact probability reaching 5.1% and the maximum horizontal impact force reaching 24.6 N. In addition, the hydraulic fluctuations caused by the suction and drainage of the cavity pipe column have a relatively small impact on the falling object trajectory. The research findings can provide practical and effective guidance for the safe construction of specific energy storage facilities, ensuring that construction can be carried out safely and efficiently, and contribute to the steady development of the energy storage industry as a whole.